2014
DOI: 10.1590/s0034-759020140103
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility practices at brazilian firms

Abstract: Práticas de responsabilidade social corporativa em empresas brasileiras RESUMOAs práticas de Responsabilidade Social Corporativa têm aumentado nos últimos anos em empresas de todo o mundo. O Brasil, um dos mais importantes países emergentes no cenário internacional, não é uma exceção a isso, com mais e mais empresas que optam por tais práticas. O presente estudo concentra-se na análise das práticas de responsabilidade social corporativa com as quais as empresas brasileiras estão envolvidas. A amostra utilizada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
3
9
0
4
Order By: Relevance
“…They found that customer health, as well as the health and safety of products and services at the different stages of the product life cycle, are the indicators most widely used by pharmaceutical and chemical as well as real state (banking and insurance) firms. Gallego-Álvarez, Formigoni, and Pompa-Antunez [29] provide similar results for Brazil. Companies located in the southeast region of the country, which accounts for more than half of the national production, including major factories and steel plants, place the greatest emphasis on social indicators related to customer health as well as public policy initiatives related to anti-corruption or anti-bribery practices.…”
Section: Previous Work and Limitationssupporting
confidence: 60%
“…They found that customer health, as well as the health and safety of products and services at the different stages of the product life cycle, are the indicators most widely used by pharmaceutical and chemical as well as real state (banking and insurance) firms. Gallego-Álvarez, Formigoni, and Pompa-Antunez [29] provide similar results for Brazil. Companies located in the southeast region of the country, which accounts for more than half of the national production, including major factories and steel plants, place the greatest emphasis on social indicators related to customer health as well as public policy initiatives related to anti-corruption or anti-bribery practices.…”
Section: Previous Work and Limitationssupporting
confidence: 60%
“…Therefore, discussing CSR implies a focus on legitimacy and competitiveness. In this sense, Gallego-Álvarez et al (2014) state that companies tend to mimic the CSR activities of local rivals in order to gain legitimacy. Goergen et al (2016) further consider sustainability and competitiveness to be necessary criteria to attain legitimacy, suggesting that a link exists between these three concepts.…”
Section: Csr As An Element Of Msmes' Legitimacymentioning
confidence: 99%
“…On the one hand, there are some studies that assume this influence by focusing only on one institutional environment (Gallego et al, 2014;Kuo, Yeh, & Yu, 2012;Michelon et al, 2015;Paul et al, 2006, Prado et al, 2009 or by controlling its effect in multinational samples (Alon, Lattemann, Fetscherin, Li, & Schneider, 2010;Chen & Bouvain, 2009;Fortanier, Kolk, & Pinkse, 2011).…”
Section: Country Selection and Samplementioning
confidence: 99%
“…This is because these country's institutional environments are clearly different (Li & Filer, 2007) and because both countries have been considered pioneers or top-ranked in the reporting of CSR information (Gallego, Formigoni, & Antunes, 2014;Grecco, Filho, Segura, García, & Rodríguez, 2013;KPMG, 2013;. Additionally, according to previous empirical evidence, there are differences concerning CG mechanisms: Brazilian companies' BDs are weaker and less effective than Spanish ones (Andrés, Azofra, & Lopez, 2005;Black, Carvalho, & Gorga, 2010).…”
Section: Introductionmentioning
confidence: 99%